MANAJEMEN PEMBERDAYAAN KOMITE SEKOLAH BERBASIS NILAI-NILAI KEARIFAN LOKAL - Akhirin Akhirin (PASCASARJANA UNISNU, 2014)
AbstractThis research describes the empowerment management of school committees based on local wisdom values. The results of this study include: 1) The school committee must be empowered in order to achieve quality education at all levels and types. School committees can be empowered if their roles and functions are properly managed, from planning, organization, implementation to evaluation. The first step is that all school committee administrators must understand their roles and functions. 2) There is a lot of local wisdom that the School Committee can use to manage this institution so that it is more empowered in carrying out its roles and functions. There are values that are commands, lessons and there are also restrictions. Some of these values come from religion and some come from customs and traditions. 3) The School Committee should be able to understand and utilize the values of local wisdom as a tool for managing the organization to be more empowered and able to carry out its roles and functions to the fullest.Keywords: empowerment management; school committee; the values of local wisdom